Assessment of Risk Factors for the Development of Late Intraocular Lens Dislocation - V. V. Potemkin; S. Yu. Astakhov; E. V. Goltsman; Syao Yu. Van (Oftalʹmologiâ)
Dislocation of intraocular lens is a serious complication of phacoemulsification with implantation of intraocular lens. Among the causes of early dislocation of intraocular lens intraoperative complications predominate, as well as various form of their mixed fixation. In the late postoperative period, dislocation of the capsular bag-intraocular lens complex mainly occurs, the main reasons for which are the zonular weakness and the failure of the capsular bag support or its fibrosis.Purpose: to assess the influence of various factors on the development of late IOL dislocation (both in the capsular bag and without it) requiring surgical correction.Patientes and methods. The study included 78 patients (78 eyes) who were underwent surgical treatment of varying degree of IOL dislocation from October 2018 to April 2020. The control group consisted of 62 patients recruited for surgical treatment of cataract at the same period. The main factors for assessment were the following: axial myopia (≥26 mm), previous vitreoretinal surgery, recurrent uveitis, primary glaucoma, retinitis pigmentosa, and the use of the capsular tension ring during phacoemulsification.Results. Among the factors studied, the following risk factors of late IOL dislocation were revealed: age, gender, the presence of pseudoexfoliation syndrome, axial myopia, primary glaucoma, implantation of the capsular tension ring. Conclusion. Phacoemulsification is the standard surgical treatment of cataract. However, in patients with potential risk factors of developing IOL dislocation, surgeons should consider the use of additional IOL fixation.